Controversy over the Round Earth and the Flat Earth on the Interpretation of the Qur'an: Study Interpretation with a Scientific Approach - Muttaqin, Rofi; Hakim, Dzikri; Fadilahi, Salman; Rafsanjani, Muhammad; Mubarok, Ade Sobur; Muhaimin, Ujang Mimin (Journal of Ulumul Qur'an and Tafsir Studies, 2022)
Abstract[Controversy over the round earth and the flat earth on the interpretation of the Qur’an: study interpretation with a scientific approach] This article discusses the interpretation related to the Qur'anic verses about the round and flat earth, through a scientific approach (bil ilmi) this study uses a qualitative method of comparative studies with shorts. The data source is the book "Tafsir ilmi" of the Ministry of Religion of the Republic of Indonesia and LIPI and "Tafsir Salman" as a comparison and equalization of the related that will be discussed.data collection techniques using the search method by means of contect analysis. This article finds that one of the problems that has been developing lately is the debate regarding the shape of our earth, whether round or flat. The knowledge that has been known to people is that the earth is round, but it also develops the understanding that the earth is flat or also called the understanding of flat earth Some scholars have actually discussed this, they are discussing the issue of the shape of the earth from the perspective of sharia.Surely they postulate with those implied in the verses of the Quran and the hadith of the Prophet Sallallahu'alaihi Wasallam which preaches about this universe. ملخص[[جدل الأرض المستديرة والأرض المسطحة في تفسير القرآن: دراسة التفسير بمنهج علم]يناقش هذا المقال تفسير آيات القرآن عن الأرض المستديرة والمسطحة من خلال منهج علمي (بالعلم) ، وتستخدم هذه الدراسة المنهج النوعي للدراسة المقارنة مع منهج مراجعة الأدبيات. مصادر البيانات هي كتاب "تفسير علمي" لوزارة الدين بجمهورية إندونيسيا و LIPI وكذلك كتاب "تفسير سلمان" كمقارنة ومعادلة فيما يتعلق بما سيتم مناقشته. تستخدم تقنية جمع البيانات طرق البحث والبيانات. تقنيات التحليل عن طريق تحليل المحتوى (تحليل المحتوى). تجد هذه المقالة أن إحدى القضايا التي يتم تطويرها حاليًا هي الجدل حول شكل أرضنا ، سواء كانت مستديرة أو مسطحة. المعرفة التي يعرفها الناس عمومًا حتى الآن هي أن الأرض كروية ، ولكن هناك أيضًا فهم بأن الأرض مسطحة أو تُعرف أيضًا باسم فهم الأرض المسطحة. لقد ناقش بعض العلماء هذا الأمر بالفعل ، فقد ناقشوا مسألة شكل الأرض من منظور شرعي. بالطبع هم افترضوا ما ورد في آيات القرآن وحديث النبي صلى الله عليه وسلم الذي بشر عن هذا الكون. Abstrak[Kontroversi bumi bulat dan bumi datar pada penafsiran Alqur’an: studi tafsir dengan pendekatan sains]Artikel ini membahas penafsiran terkait ayat Al-qur’an tentang bumi bulat dan datar, dengan melalui pendekatan sains (bil ilmi) kajian ini menggunakan metode kualitatif studi komparasi dengan pendekatan kajian pustaka. Sumber data merupakan buku “Tafsir ilmi” kemenag RI dan LIPI serta “Tafsir Salman”sebagai perbandingan dan menyamakan terkait yang akan dibahas.tehnik pengumpulan data menggunakan cara penelusuran dan tehnik analisis data dengan cara analisis isi (contect analysis). Artikel ini menemukan bahwa salah satu masalah yang sedang berkembang akhir-akhir ini adalah perdebatan mengenai bentuk bumi kita, apakah bulat ataukah datar. Pengetahuan yang selama ini diketahui umumnya orang adalah bahwa bumi itu bulat, namun berkembang juga pemahaman bahwa bumi itu datar atau disebut juga pemahaman flat earth. Beberapa ulama sebenarnya telah membahas hal ini, mereka membahas masalah bentuk bumi dari perspektif syariat. Tentunya mereka berdalil dengan yang tersirat dalam auat-ayat Al-Quran dan hadits Nabi Shallallahu’alaihi Wasallam yang mengabarkan tentang alam semesta ini.